Evaluating the effects of nacre on human skin and scar cells in culture. Issue 4 (16th May 2014) - Agarwal, Vipul; Tjandra, Edwin S.; Iyer, K. Swaminathan; Humfrey, Barry; Fear, Mark; Wood, Fiona M.; Dunlop, Sarah; Raston, Colin L.
Graphical Abstract: Abstract: Pearl nacre, a biomineralisation product of molluscs, has growing applications in cosmetics, as well as dental and bone restoration, yet a systematic evaluation of its biosafety is lacking. Here, we assessed the biocompatibility of nacre with two human primary dermal fibroblast cell cultures and an immortalised epidermal cell line and found no adverse effects.